Comprehensive analysis of the biological functions of endoplasmic reticulum stress in prostate cancer - Cen, Shengren; Jiang, Dongmei; Lv, Daojun; Xu, Ran; Hou, Jiamao; Yang, Zixiang; Wu, Peng; Xiong, Xinhao; Gao, Xingcheng (Frontiers in Endocrinology, 2023)
Endoplasmic reticulum stress (ERS) has sizeable affect on cancer proliferation, metastasis, immunotherapy and chemoradiotherapy resistance. However, the effect of ERS on the biochemical recurrence (BCR) of prostate cancer patients remains elusive. Here, we generated an ERS-related genes risk signature to evaluate the physiological function of ERS in PCa with BCR. We collected clinical information and genomic profiles from TCGA and GEO databases. The ERS risk signature was created with the differentially expressed ERS-related genes in PCa by the LASSO and multivariate Cox regression model. Nomogram was developed to assess BCR-free survival possibility. Meanwhile, correlations between ERS-related signature, gene mutations, drug sensitivity and tumor microenvironment were also investigated. Finally, we obtained an ERS risk signature consisting of five genes (AFP, COL10A1, DNAJB1, EGF and PTGS2). Kaplan Meier survival analysis and ROC Curve analyses indicated that the ERS-related gene signature with high-risk score was associated with poor BCR-free prognosis in PCa patients. Besides, immune cell infiltration and immune checkpoint expression levels differed between high- and low-risk scoring subgroups. Moreover, drug sensitivity analyzed indicated that high-risk score group may be involved in apoptotic pathway. In conclusion, our research comprehensively analyzed the characteristics of ERS-related genes signature in PCa, which may provide potential guidance for the future treatment of PCa.